The Semantic Analysis of Joko Widodo’s Speech on Youtube - Agustinus Givano (CV. Tirta Pustaka Press, 2023)
In this research, there are several expressions of words that are grammatically used in semantic meaning in Joko Widodo's speech discourse. The data analysis technique used is qualitative descriptive analysis from 10 data on the title Jokowi speech on YouTube and obtained from the observation method. In its disclosure, five types of semantic meaning have been found, namely conceptual meaning, connotative meaning, social meaning, effective meaning and thematic meaning. The type of meaning that is often found is conceptual meaning (38.20%). To follow the flow in a speech script, we can analyze the semantic meaning in it. A speech is a formal presentation given to the audience. A speaker can deliver a good speech as long as the speaker focuses on his goal and tries to convey the goal in the minds of the audience. But sometimes the audience cannot understand what the speaker is saying. In this case, semantic meaning and speech are important things to be researched and studied in depth when applied to social linguistics.